Green economy: Islamic social reporting for companies - Tri Wahyudi; Nur Sabrina; Camka Ayu Pratiwi (Journal of Islamic Accounting and Finance Research, 2023)
Purpose - The purpose of this study is to examine the impact of Islamic social reporting on firm value.Method - This research uses quantitative methods. The sample in this study is 13 sharia companies registered in the Jakarta Islamic Index for 2016-2020. Data analysis using multiple linear regression. Islamic social reporting as an independent variable, while the firm value is measured using Tobin's Q as the dependent variable, and firm size as a control variable.Result - The empirical results in this study found that Islamic social reporting has a positive and significant effect on firm value.Implication - Sharia companies listed in the Jakarta Islamic Index are expected to focus on Islamic principles in carrying out activities including in social aspects to increase company value as part of the company's strategy.Originality - This study combines the ISR disclosure index from several previous researchers to measure ISR disclosure in Islamic companies.